Clinical Manifestations and Distribution of Cutaneous Leishmaniasis in Pakistan - Abaseen Khan Afghan; Masoom Kassi; Pashtoon Murtaza Kasi; Adil Ayub; Niamatullah Kakar; Shah Muhammad Marri (Journal of Tropical Medicine)
Cutaneous leishmaniasis (CL) is a rising epidemic in Pakistan. It is a major public health problem in the country especially alongside regions bordering the neighboring Afghanistan and cities that have had the maximum influx of refugees. The purpose of our paper is to highlight the diverse clinical manifestations of the disease seen along with the geographic areas affected, where the hosts are particularly susceptible. This would also be helpful in presenting the broad spectrum of the disease for training of health care workers and help in surveillance of CL in the region. The increased clinical diversity and the spectrum of phenotypic manifestations noted underscore the fact that the diagnosis of CL should be not only considered when dealing with common skin lesions, but also highly suspected by dermatologists and even primary care physicians even when encountering uncommon pathologies. Hence, we would strongly advocate that since most of these patients present to local health care centers and hospitals, primary care practitioners and even lady health workers (LHWs) should be trained in identification of at least the common presentations of CL.